Psychological Factors as Predictors of High-Quality Achievement in Biology - Olosunde, Michael; Babatunde, Ezekiel Olusegun (Universitas Islam Negeri Walisongo Semarang, 2025)
One of Nigeria's biggest challenges is achieving Sustainable Development Goal (SDG) 4, which calls for providing inclusive and equitable quality education and promoting lifelong learning opportunities for all even with onboarding of Artificial Intelligence. This study investigates how psychological factors influence student success in biology, an important scientific field. The study considered three research questions using non experimental research design of correlational approach, conducted with 400 senior secondary school students from Oyo State, Nigeria. Four instrument used are: Biology Interest Scale (BIS) with α=0.91, Anxiety Traits Inventory (ATI) α=0.74, Academic Motivation Scale (AMS) α=0.87 and Biology Achievement Test (BAT) with 0.80. Result revealed a high link between biology achievement and motivation (r = .187, p < .01), interest (r = .253, p < .01), and anxiety (r = - 0.272, p < .01). Moreover, there was significant effect (F(3, 396) = 16.748, p < 0.001) between variables. Students that were enthusiastic performed better, (β= 0.058, F(3, 396)=.556), indicates no statistically significant effects despite the positive relationship between achievement scores and motivation. In order to achieve Sustainable Development Goal 4 (SDG 4), which calls for inclusive and equitable quality education, affective elements that affect the participation of learners in biology, such as anxiety and interest, must be addressed. Supportive learning environments that prioritize understanding, curiosity, and personal development should be created by educators and policymakers. Integrating real-world biological applications into the curriculum can further enhance the subject’s relevance to everyday life and future careers, thereby sustaining students’ motivation and interest in biology.